Understanding geographical imbalances in the health workforce - Serneels, P; Barr, A; Lindelow, M (University of Oxford, 2005)
Geographical imbalances in the health workforce have been a consistent feature of nearly all health systems, and especially in developing countries. In this paper we investigate the willingness to work in a rural area among final year nursing and medical students in Ethiopia. Analyzing data obtained from contingent valuation questions, we find that household consumption and the student's motivation to help the poor, which is our proxy for intrinsic motivation, are the main determinants of willingness to work in a rural area. We investigate who is willing to help the poor and find that women are significantly more likely than men. Other variables, including a rich set of psycho-social characteristics, are not significant. Finally, we carry out some simulations on how much it would cost to make the entire cohort of starting nurses and doctors choose to take up a rural post.